Cover Picture: Three‐dimensional Porous Palladium Foam‐like Nanostructures as Electrocatalysts for Glucose Biofuel Cells (Energy Technol. 2/2016). Issue 2 (12th January 2016) - Zhao, Yue; Fan, Louzhen; Hong, Bo; Zhang, Yang; Zhang, Minsheng; Que, Qiming; Ji, Junyuan
Abstract : Conversion materials: Three‐dimensional (3D) porous palladium (Pd) nanostructures are electrodeposited by using an improved hydrogen template protocol, involving a reduction, the key step of potential pulse. The application of a three‐dimensional (3D) porous palladium nanostructure for implantable enzyme‐free glucose biofuel cells (GBFCs) with simple fabrication protocols, good performance (high power density of 5.7±0.4 μW cm ‐2 and an open‐circuit potential 0.650±0.005 V in a physiological environment), and satisfactory stability (<10 % degradation in 30 days) was demonstrated. This new procedure yields benefits such as rapid fabrication, mild conditions, pure products with a unique 3D porous structure, and the identical preparation technology used for both the anode and cathode. More details can be found in the Communication by Junyuan Ji of the Ocean University of China and co‐workers onpage 249 in Issue 2, 2016 (DOI:10.1002/ente.201500386 ).